Junction formation and current transport mechanisms in hybrid n-Si/PEDOT:PSS solar cells - Jaeckle, Sara; Mattiza, Matthias; Liebhaber, Martin; Broenstrup, Gerald; Rommel, Mathias; Lips, Klaus; Christiansen, Silke (Scientific Reports, 2015)
We investigated hybrid inorganic-organic solar cells combining monocrystalline n-type silicon (n-Si) and a highly conductive polymer poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonate) (PEDOT:PSS). The build-in potential, photo- and dark saturation current at this hybrid interface are monitored for varying n-Si doping concentrations. We corroborate that a high build-in potential forms at the hybrid junction leading to strong inversion of the n-Si surface. By extracting work function and valence band edge of the polymer from ultraviolet photoelectron spectroscopy, a band diagram of the hybrid n-Si/PEDOT:PSS heterojunction is presented. The current-voltage characteristics were analyzed using Schottky and abrupt pn-junction models. The magnitude as well as the dependence of dark saturation current on n-Si doping concentration proves that the transport is governed by diffusion of minority charge carriers in the n-Si and not by thermionic emission of majorities over a Schottky barrier. This leads to a comprehensive explanation of the high observed open-circuit voltages of up to 634 mV connected to high conversion efficiency of almost 14%, even for simple planar device structures without antireflection coating or optimized contacts. The presented work clearly shows that PEDOT:PSS forms a hybrid heterojunction with n-Si behaving similar to a conventional pn-junction and not, like commonly assumed, a Schottky junction.
EAM Import::2019-03-12